Preliminary Diagnosis and Characterization of a Spontaneous Immature Testicular Teratoma in an Interferon Receptor-Deficient Mouse Model - ZHAO He; ZHANG Fan; XIAO Yuzhou; AN Xuefang; ZHANG Tao; LI Li (Shiyan dongwu yu bijiao yixue)
ObjectiveTo observe the spontaneous testicular tumors in interferon receptor-deficient mice (AG129) and provide a basis for further research using this mouse strain.MethodsThe AG129 mouse population was bred in an SPF barrier environment and reproduced normally. Among the 3-week-old weaned mice, we found that one male mouse had an abnormally enlarged testis, while none of the other mice in the same litter exhibited a similar condition. The spontaneous testicular tumor in this mouse was continuously monitored. The mouse was euthanized and dissected at 9 weeks of age. The gross morphology of the tumor was observed, and the tissue was then embedded in paraffin and sectioned for hematoxylin and eosin (HE) staining.ResultsAfter several weeks of observation, the tumor tissue gradually increased in size as the mice aged. Upon dissection, the tumor tissue was encapsulated in a smooth capsule. After opening the capsule, the tumor tissue was irregular in shape, with some areas being hard and others soft. The results of HE staining showed that the tumor tissue developed from tissues derived from multiple germ layers, with nerve tissue, bone tissue, muscle tissue, and adipose tissue inside, exhibiting an irregular morphological structure.ConclusionBased on the tumor development, gross morphological structure, and the HE staining results of the pathological sections, the tumor in this mouse was preliminarily diagnosed as an immature teratoma.